The development of student-teachers' professional identity while team-teaching science classes using a project-based learning approach: A multi-level analysis. (March 2019) - Tsybulsky, Dina; Muchnik-Rozanov, Yulia
Abstract: The research study deals with the development of professional identity of 17 student-teachers during their pedagogical practicum while team-teaching science classes using a project-based learning (PBL) approach. Data were collected from in-depth interviews as well as reflective reports and analyzed by means of multilevel analysis. Findings indicate that the student-teachers' professional identity was shaped by meaningful experiences in two dimensions: overcoming challenges while leading PBL and involvement in fruitful and supportive cooperation with their peers. The student-teachers progressed from group-focused to self-focused professional identity, indicating professional growth, empowerment, and substantial gains in self-confidence. Highlights: Team-teaching PBL in science classes helped shape student-teachers' professional identity. The development of the student-teachers' professional identity was associated with three major types of experience. Team-teaching PBL resulted in a shift from group-focused to self-focused identity. The overall outcome was noticeable professional growth, empowerment, and gains in student-teachers' self-confidence.